2007
DOI: 10.1126/science.1135459
|View full text |Cite
|
Sign up to set email alerts
|

Atom Interferometer Measurement of the Newtonian Constant of Gravity

Abstract: We measured the Newtonian constant of gravity, G , using a gravity gradiometer based on atom interferometry. The gradiometer measures the differential acceleration of two samples of laser-cooled Cs atoms. The change in gravitational field along one dimension is measured when a well-characterized Pb mass is displaced. Here, we report a value of G = 6.693 × 10 –11 cubic meters per kilogram second squared, with a standard error of the mean of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
438
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(448 citation statements)
references
References 20 publications
8
438
0
2
Order By: Relevance
“…[1], a 3 parts per billion (ppb) modulation in local gravity leads to a 1% shift of the interference fringe. They thus make excellent microscopes for small signals that have been applied in many cutting-edge precision measurements [1][2][3][4][5][6][7][8][9][10]. Large-momentum transfer (LMT) beam splitters, which have become practical recently [11], promise to increase the sensitivity further, by factors of 10s to 100s, by increasing the space-time area enclosed between the interferometer arms.…”
mentioning
confidence: 99%
“…[1], a 3 parts per billion (ppb) modulation in local gravity leads to a 1% shift of the interference fringe. They thus make excellent microscopes for small signals that have been applied in many cutting-edge precision measurements [1][2][3][4][5][6][7][8][9][10]. Large-momentum transfer (LMT) beam splitters, which have become practical recently [11], promise to increase the sensitivity further, by factors of 10s to 100s, by increasing the space-time area enclosed between the interferometer arms.…”
mentioning
confidence: 99%
“…It should be observed that there are still large measurement errors in the gravitational constant; see [13][14][15][16][17].…”
Section: Mcculloch-heisenberg Newton Equivalent Gravitymentioning
confidence: 99%
“…The value of this constant is not very accurately known, and the different values we can find in the literature can have an impact on the frequency calculation of the same order or even larger than the differences studied here. To illustrate this, two extreme values of G found in the literature have been chosen: G 1 = 6.6716823 × 10 −8 cgs (as fixed for Task 1), and G 2 = 6.693 × 10 −8 cgs (Fixler et al, 2007), the most recent one, although with a quoted random error of ±0.027 × 10 −8 and a systematic error of ±0.021 × 10 −8 cgs it is consistent with the previous value. The present recommended value of the Committee on Data for Science and Technology (CODATA) can be found in the World Wide Web at physics.nist.gov/constants, and it is closer to that fixed in Task 1.…”
Section: Computational Variationsmentioning
confidence: 99%